Lung Ultrasound for Imaging of B-Lines in Dogs and Cats—A Prospective Study Investigating Agreement between Three Types of Transducers and the Accuracy in Diagnosing Cardiogenic Pulmonary Edema, Pneumonia and Lung Neoplasia - Andrzej Łobaczewski (MDPI AG, 2021)
Transthoracic heart and lung ultrasound (LUS) was performed in 200 dogs and cats with dyspnea to evaluate the agreement between the results obtained using three types of transducers (microconvex, linear, and phased array) and to determine the accuracy of LUS in discriminating between three conditions commonly causing dyspnea in companion animals: cardiogenic pulmonary edema (CPE), pneumonia, and lung neoplasm. The agreement beyond chance was assessed using the weighted Cohen’s kappa coefficient (κw). The highest values of κw (>0.9) were observed for the pair of microconvex and linear transducers. To quantify B-lines the lung ultrasound score (LUSscore) was developed as a sum of points describing the occurrence of B-lines for each of 8 standardized thoracic locations. The accuracy of LUSscore was determined using the area under ROC curve (AUROC). In dogs AUROC of LUSscore was 75.9% (CI 95%: 65.0% to 86.8%) for distinguishing between lung neoplasms and the two other causes of dyspnea. In cats AUROC of LUSscore was 83.6% (CI 95%: 75.2% to 92.0%) for distinguishing between CPE and the two other causes of dyspnea. The study shows that results obtained with microconvex and linear transducers are highly consistent and these two transducers can be used interchangeably. Moreover, the LUSscore may help identify dogs with lung neoplasms and cats with CPE, however its diagnostic accuracy is only fair to moderate.